Interpretation of Educational Verses Study of the Interpretation of Q.S Al-Baqarah 30-34 (Value and Implications in the World of Islamic Education) - Kanus, Oktari (Universitas Negeri Padang, 2023)
Religious education is a process of teaching, educating and character building as well as stimulating human instincts in realizing awareness of worshiping Allah in order to understand the purpose of humans as abdun. This research aims to analyze, interpret and describe the values of religious education contained in Q.s al-Baqarah: 30-34. The research method used in this research is a qualitative method using a library research approach (library study) through various sources of books, manuscripts, journals sourced from the literature. The research findings show the values of religious education contained in it: first, moral education, namely the morals of a student towards a teacher, morals in seeking knowledge and the prohibition against being arrogant. Second, religious education, that is, people with knowledge are more noble than people without knowledge, which is why Prophet Adam should be made caliph because the knowledge he possessed was more extensive than that of the angels. The results of this research can be used as information for the public so they can understand the meaning and interpretation of these verses regarding worship education.